أثر برنامج مقترح للأنشطة البدنية والرياضية في تنمية التصور العقلي لدى تلاميذ التعليم المتوسط - خضراوي, نبيل (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة إلى معرفة أثر النشاط البدني الرياضي على التصور العقلي،حيث إستخدم الباحث المنهج التجريبي لملائمته لطبيعة الدراسة (تصميم المجموعتين) ويمثل مجتمع البحث تلاميذ التعليم المتوسط،أخذت منه عينة قصدية(عمدية) بلغت (26) تلميذ تم تقسيمها بالتساوي إلى مجموعتين (تجريبية، ضابطة)،ولجمع المعلومات والبيانات إعتمد الباحث على الأدوات التالية:مقياس التصور العقلي في المجال الرياضي الذي وضعه مارتنز (1982)وقام بتعريبه وتقنينه محمد العربي شمعون وماجدة إسماعيل سنة (1996) ،وتم معالجة البيانات والمعلومات بإستخدام برنامج الحزمة الإحصائية للعلوم الإجتماعية(SPSS) وبإستخدام الأساليب الإحصائية التالية: المتوسط الحسابي،الإنحراف المعياري، إختبار Man-Whitney U)). ومن نتائج الدراسة مايلي: •للبرنامج المقترح تأثير إيجابي على نمو التصور العقلي لدى تلاميذ التعليم المتوسط . Abstract: The study aims to know the effect of physical and sports activities on mental perception where the researcher used the experimental approach for its suitability to the nature of the study, the research community is represented by middle school pupils, from whom an intentional sample of (26) pupils were taken and divided equally into two groups (experimental - witness), and to collect information and data, the researcher relied on the following tools: mathematical mental perception scale developed by (Martens1982) was Arabized and legalized by Muhammad Al-Arabi Shimoun and Majda Ismail in the year (1996),the data and information has been processed using the social Sciences Statistical Package Program (SPSS), in addition to the following statistical methods : Arithmetic average, standard deviation, test )Man-Whitney U( and the results of the study include: The proposed program has a positive impact on the development of mental skills (focus attention, mental perception, relaxation) among middle school pupils.
The effect of a proposed program for physical activities and sports on developing the of mental perception among intermediate education pupils
مقال
Keywords: البرنامج، النشاط البدني الرياضي، المهارة العقلية، التصور العقلي ، المراهقة; program , physical sportif activity, mental skill, mental perception, adolescence.